Effects of packaging materials and storage conditions on storability of pepper (Capsicum frutescens L.) fruits - Adewoyin , O B (Journal of Postharvest Technology, 2017)
Pepper is a perishable seasonal vegetable fruit that requires appropriate postharvest handling and storage to extend its shelf-life and preserve  quality of the Pepper Fruit (PF). However, there is dearth of information on its handling and storage in Southwest Nigeria. Pepper grown in the  organic field, Teaching and Research Farm, Federal University University, OyeEkiti were harvested with and without pedicels at 10 and 100%  ripeness. Postharvest handling was evaluated by comparing packaging in perforated polyethylene, non-perforated polyethylene and  aluminium-foil before storing in either Ambient Conditions (AC) of 21.9-33.5°C and 58-62% Relative Humidity (RH); Refrigerator (4.0°C and  40-45% RH) or Evaporative Coolant Structure (ECS) (10.0-15.8°C and 70-75% RH). Percentage Weight Loss (WL) was calculated. Firmness  (FM) and Decay Level (DL) were evaluated on a scale of 1 to 4 and General Appearance (GA) on scale of 1 to 5. Data were analysed using  correlation coefficient and ANOVA at p
Keywords: Pepper storability; Packaging; Capsicum frutescens; Postharvest; Quality